2001
DOI: 10.5194/angeo-19-1163-2001
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric ozone depletion during the 1995–1996 Arctic winter: 3-D simulations on the potential role of different PSC types

Abstract: Abstract. The sensitivity of modelled ozone depletion in the winter Arctic stratosphere to different assumptions of prevalent PSC types and PSC formation mechanisms is investigated. Three-dimensional simulations of the winter 1995/96 are performed with the COlogne Model of the Middle Atmosphere (COMMA) by applying different PSC microphysical schemes. Model runs are carried out considering either liquid or solid PSC particles or a combined microphysical scheme. These simulations are then compared to a model run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The reaction scheme comprises 167 gas‐phase reactions (see Tables 1 and 2) and 10 heterogeneous reactions on surfaces of Polar Stratospheric Cloud (PSC) particles and in sulphate aerosol droplets (see Table 3). The mechanism follows partly Hendricks et al [2001], with extensions for the upper stratosphere and lower mesosphere. Reaction velocities follow recommendations from Sander et al [2006].…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction scheme comprises 167 gas‐phase reactions (see Tables 1 and 2) and 10 heterogeneous reactions on surfaces of Polar Stratospheric Cloud (PSC) particles and in sulphate aerosol droplets (see Table 3). The mechanism follows partly Hendricks et al [2001], with extensions for the upper stratosphere and lower mesosphere. Reaction velocities follow recommendations from Sander et al [2006].…”
Section: System Descriptionmentioning
confidence: 99%
“…N sulf = 5 cm −3 was taken as a representative number density for stratospheric aerosols [ Deshler et al , 2003]. Following Hendricks et al [2001], PSC particle number densities are prescribed by N NAT = 1 cm −3 and N ice = 0.01 cm −3 .…”
Section: System Descriptionmentioning
confidence: 99%
“…The region where PSC fields are the most difficult to model is the Arctic lower stratosphere [ Hendricks et al , 2001; Carslaw et al , 2002; Fueglistaler et al , 2003]. In contrast to the Southern Hemisphere, the Arctic temperatures are usually quite variable in space and time.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to chlorine activation, PSC particles may also promote polar ozone destruction by denitrifying the polar stratosphere. , The degree of denitrification and halogen activation on PSC particles is important for determining the severity of polar ozone loss and depends strongly on the formation mechanism and type of PSC. , Large NAT particles are more efficient at depleting nitric acid than either NAD or supercooled ternary solutions. ,, Severe denitrification occurs when NAT particles grow to sizes larger than 5 μm in radius. , Currently, there is no established nucleation mechanism that sufficiently explains the formation of these large NAT particles. ,, Homogeneous nucleation from supercooled ternary solutions is probably too slow to form large nitric acid-containing particles . Additionally, previous field studies have found that the presence of ice was not necessary for the formation of large NAT particles .…”
Section: Introductionmentioning
confidence: 99%
“…4,15 The degree of denitrification and halogen activation on PSC particles is important for determining the severity of polar ozone loss and depends strongly on the formation mechanism and type of PSC. 16,17 Large NAT particles are more efficient at depleting nitric acid than either NAD or supercooled ternary solutions. 12,18,19 Severe denitrification occurs when NAT particles grow to sizes larger than 5 µm in radius.…”
Section: Introductionmentioning
confidence: 99%